Organizational Culture in Education: Components, Influences, and Improvement Strategies through a Literature Review - Zohriah, Anis; Holid, Agus; Gunawan, Agus; Fauzi, Anis (CV. Strata Persada Academia, 2025)
This study investigates the complex nature of organizational culture in educational institutions by analyzing its core components, influencing factors, and strategic improvement approaches through a systematic literature review. Recognizing the pivotal role of organizational culture as a determinant of institutional effectiveness, this research synthesizes theoretical perspectives and empirical findings from peer-reviewed studies published between 2013 and 2023. Guided by PRISMA protocols, the review encompasses literature sourced from major academic databases, including, SINTA, Garuda, Scopus, Web of Science, ERIC, and ScienceDirect, and applies thematic analysis to extract patterns, frameworks, and practical insights. The findings reveal that organizational culture in education is constituted by interrelated elements—values, norms, artifacts, and assumptions—which collectively shape institutional behavior, learning environments, and stakeholder interactions. When strategically aligned with institutional goals, these cultural components foster a collaborative climate, enhance teacher motivation and student outcomes, and contribute to conflict resolution and institutional resilience. The study concludes that the cultivation of a coherent and strategically reinforced culture, supported by transformative leadership and inclusive communication, is essential for achieving sustainable educational excellence. The research provides a comprehensive conceptual framework and offers actionable recommendations for educational leaders and policymakers to embed culture as a strategic lever for systemic improvement in dynamic and competitive educational contexts.